Impact analysis in the presence of dependence clusters using Static Execute After in WebKit. Issue 6 (12th September 2013) - Schrettner, Lajos; Jász, Judit; Gergely, Tamás; Beszédes, Árpád; Gyimóthy, Tibor; Ceccato, Mariano; Li, Zheng; Cordy, James R.
SUMMARY Impact analysis based on code dependence can provide opportunities to identify parts of the software affected by a change. Because changes usually have far reaching effects in programs, effective and efficient impact analysis is vital. Static Execute After (SEA) is a relation on procedures that is efficiently computable and accurate enough to be a candidate for the use in impact analysis in practice. To assess the applicability of SEA in terms of capturing real defects, we present results on integrating it into the build system of WebKit, a large, open source software system, and on related experiments. We show that a large number of real defects can be captured by impact sets computed by SEA, albeit many of them are large. We demonstrate that this is not an issue in applying it to regression test prioritization, but generally it can be an obstacle in the path to efficient use of impact analysis. We believe that the main reason for large impact sets is the formation of dependence clusters in code. As apparently dependence clusters cannot be easily avoided in the majority of cases, we focus on determining the effects these clusters have on impact analysis and regression test prioritization. Copyright © 2013 John Wiley & Sons, Ltd.